THE CHARACTERISTICS OF SAGO CRACKERS (Metroxylon sp.)FORTIFIEDWITH SHRIMP REBON (Mysis relicta) PROTEINHYDROLYZATE - Siregar, Heppi Nurjanah; Dewita, Dewita; Suparmi, Suparmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT              This study aimed to determine the best concentration of shrimp rebon (Mysis relicta) protein hydrolyzateand the characteristics of sago crackers (Metroxylonsp.) fortified with the shrimp protein hydrolyzate. The method used was the experimental and composed as a non-factorial Completely Randomized Design (CRD). The treatment conducted was fortification of shrimp protein hydrolyzate at a different concentration (0%, 5%, 10%, and 15%) to the sago flour to produce the highest quality of the crackers. The parameters observed were the proximate composition, including the content of water,ash, fat, protein, carbohydrate; the puffingstrength; and an organoleptic value (color, aroma, taste and crispness) of the crackers produced. The results showed that the treatment of fortification with 15% shrimp protein hydrolyzate was producing the best crackers. The best product was characterized with brownish-white features and very interesting appearance, shrimprebon flavored, highly tasted of shrimprebon, and very crunchy. It was showing the puffing strength at 327.92% and the proximate composition, including the content of water 7.65%, ash 1.41%, fat 0.46%, protein 18.35%, carbohydrate 72,11% and growth power 327.92%. Keywords: fortification, protein hydrolyzate, sago crackers.